TARI KAIN PADA UPACARA BEGAWAI SUKU TALANG MAMAK DI KABUPATEN INDRAGIRI HULU - Susi "; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in the village of Indragiri Hulu Regency Gutter Jerinjing. The purpose of this research is to know the role of customs in the implementation of dance fabrics in the implementation of the gadget in the village of Talang Jerinjing. Topic the focus of this research is to know the meaning of each of the symbols used on the dance fabrics in the implementation of the gadget in the village of Talang Jerinjing. The sample in this research totalled 5. The author uses qualitative methods and use techniques the taking of purposive sampling. Data instruments are observation, interview and documentation. From the research that is done, the author finds there are several meanings of Dance Fabrics On Gawai Talang Mamak Tribes i.e. Marriage as follows: motion, movement in the dance of the fabric means that all existing in motion dance fabrics, cannot be separated from elements the beauty and also the cultural values of the indigenous Talang Mamak tribes especially for brides who marry. In the property, property in dance Fabrics should be equipped, namely: cloth Gloves, cloth themselves aprons/Off/Tarap and Headband/head of Tapas. If the third object does not complete then it's effect on the bride. Many of the result obtained and felt on this custom event if the bride does not comply with the established customs that his life ntah not harmony. In music, dance Fabrics For the use of this instrument only as a counterpoint to the dance. However, in the procession of the second use of the Gadget's own instrument effect on brides who are getting married. One of them at a time when food named this sdah arise from migration is finished cooking, and was about to be brought into the home is obliged to emit music. Therefore the last historically otherwise sounding music, later susatu the moment the bride have children, children belonging to them that no hearing/sensitive. So it is required according to the custom. Keywords: Talang Mamak, Tribes, , Dance Fabrics